2022
DOI: 10.1155/2022/7651215
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Stone Removal via Different Approaches in the Treatment of Incarcerated Upper Ureteral Calculi: A Comparative Study

Abstract: Objective. The aim of this study is to investigate the clinical effects of percutaneous nephrolithotomy and transurethral ureteroscopic lithotripsy in the treatment of incarcerated upper ureteral calculi. Methods. This study retrospectively reviewed 400 patients with incarcerated upper ureteral calculi admitted to the hospital from January 2016 to December 2021. Among them, 200 patients treated with percutaneous nephrolithotomy were included in the percutaneous group and 200 patients treated with transurethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In our study, the occurrence of post-PCNL pain was found to be independent of the patient's age, gender, BMI, preoperative urine culture, preoperative blood creatinine, and location of the stone, which is also consistent with the results of previous studies. [3,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the occurrence of post-PCNL pain was found to be independent of the patient's age, gender, BMI, preoperative urine culture, preoperative blood creatinine, and location of the stone, which is also consistent with the results of previous studies. [3,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the stone and the surgical approach may lead to different operative time. Yuan et al [12] showed that PCNL was associated with a longer operative time and hospital stay but lower postoperative complication rate than transurethral urethroscopic lithotripsy. A meta-analysis [23] indicated that standard and mini PCNL was not signi cantly different in terms of postoperative pain, fever, complications, and duration of operation.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%